OPTIMALISASI SEGMEN BISNIS ISLAM DALAM PENINGKATAN KINERJA FUNDING DI BANK MUAMALAT KH. MAS MANSYUR SURABAYA - Amin, Rukhul (Jurnal Masharif Al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The expanding development of Islamic banking necessitates that every Islamic bank has the best strategies to market its products. This is why Bank Muamalat KH. Mas Mansyur has chosen a market mapping strategy. The market segmentation targets the Islamic business segment. This strategy is selected based on the large Muslim population in Indonesia, which is currently the majority. The research problem is centered on the funding strategy within the Islamic business segment to enhance third-party fund collection at Bank Muamalat KH. Mas Mansyur Surabaya, as well as analyzing the implementation of this strategy. The aim of this study is to understand the funding strategy applied by Bank Muamalat KH. Mas Mansyur Surabaya in the Islamic business segment to increase third-party fund collection. The research method used in this study is qualitative, with a field research approach. The researcher will directly engage in fieldwork to conduct observations and data collection. The data will be sourced from both primary and secondary data. Data collection techniques will include interviews with several informants, observations and documentation. The analysis process will begin with data collection, followed by data reduction to select key information, presentation of the data, and finally drawing conclusions. The findings of this study indicate that the strategy currently implemented by Bank Muamalat KH. Mas Mansyur Surabaya, which is market mapping in the Islamic sector, is an appropriate strategy for funding product marketing at the bank. However, the increase in third-party funds is still somewhat fluctuating and faces several challenges in practice.